The Interesting Da'wah Programmes for the Muallaf in Islamic Religion Council and the Malay Custom of Kelantan (MAIK) - Azlinda Bt Aziz (Universiti Sains Islam Malaysia, 2010)
The title of academic project is "THE INTERESTING DA'WAH PROGRAMMES FOR THE MUALLAF IN MAJLIS AGAMA ISLAM DAN ADAT ISTIADAT MELAYU KELANTAN (MAIK)". This academic project discuss about da'wah programs from MAIK,s Da'wah Unit. Usually this programmed focused to Muallaf that involve many types of programs such as Fardhu Ain program, Islamic approachment, celebration for Islamic festival and so on. Beside that, it also studies about Muallaf opinion that involve about their problems and acceptance with this programs under the MAIK's dakwah unit. Library research, interviews and questionnaire relevant methods are the tools employed for data gathering purpose. Beside that, this research unit discuss about the background of MAIK, the role of MAIK and the position of Dakwah Unit in this organization. This research also discusses about the position of Muallaf in Islam and the methodology that has been used to invite and attract them about the strength of Islam religion. Beside that this research has listed all MAIK's programs which are involving the participation of Muallaf. It also discussed about the problems that has been faced by MAIK's dakwah unit regarding the Muallaf. In this research, the writer hopes that academic project should give the contribution to knowledge. Hopefully Islamic knowledge will spread and can give many benefits in our lives.